Focus group discussion UiTM-USU SRP Research Grant 5th September 2023 / Saiful Bahri Mohd Kamal … [et al.] - Mohd Kamal, Saiful Bahri; Azmi, Azila; Sulaiman, Suria; Ramaiah, Angayar Kanni; Mat Isa, Norshamshina (UiTM Global @ Office of International Affairs, 2024)
On 5 September 2023, a group of researchers from Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, and Perlis Branch were invited to Medan, Indonesia, for a focus group discussion (FGD) with industry professionals. The FGD was part of a collaborative research project between UiTM and the Faculty of Law at Universitas Sumatera Utara (USU). The research is funded by the UiTM Strategic Research Partnership (SRP) Grant and the USU TALENTA Grant. Several stakeholders in the tourism sector in Medan were identified and interviewed during the FGD. This FGD was also held in conjunction with the 'Academic Nexus Programme (ANP): Catalysing Research Collaboration through USU-UiTM,' which was held from 4 to 10 September 2023. This FGD is an ongoing research activity that began in March 2023. Before the FGD, the initial investigation was conducted in USU, Samosir, and Parapat between 12 and 17 March 2023. The data collected during the visit has been published in two WOS-indexed proceedings.